SEL Series Expansion and Generalized Model Construction for the Real Number System via Series of Rationals - Patiwat Singthongla; Narakorn Rompurk Kanasri (International Journal of Mathematics and Mathematical Sciences)
We present an algorithm for constructing infinite series expansion for real numbers, which yields generalized versions of three famous series expansions, namely, Sylvester series, Engel series, and Lüroth series expansions. Using series of rationals, a generalized model for the real number system is also constructed.